STUDI KEKUATAN TARIK KOMPOSIT SERAT JERAMI PADI YANG DIBUAT DENGAN METODE VACUUM BAGGING - Saputra, Fadhliansyah Ramadhan; Setiawan, Hery; Parman, Setyamartana; Karnaen, Irfan Abdulhafizh (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
This study aims to determine the effect of rice straw fiber orientation on the tensile strength of composite materials manufactured using the vacuum bagging method. The composites were made using rice straw fibers arranged in two orientations: parallel and random, with epoxy resin as the matrix. Specimens were produced according to ASTM D638 Type 1 standards and tested using a tensile testing machine. The results revealed that fiber orientation significantly influences tensile strength. The parallel fiber specimens achieved an average tensile strength. The parallel fiber specimens achieved an average tensile strength of 22.54 Mpa, significantly higher than the random fiber specimens which only reached 1.68 Mpa. The tensile strength difference between the two orientations was 20.86 Mpa. The tensile strength difference between the two orientations was 20.86 Mpa. It can be concluded that parallel fiber alignment provides better mechanical performance, making it more suitable for structural applications that require high tensile strength.